2010
DOI: 10.1002/eqe.1087
|View full text |Cite
|
Sign up to set email alerts
|

Extension of the CSM-FEMA440 to plan-asymmetric real building structures

Abstract: SUMMARYThe capacity spectrum method (CSM) has established itself as one of the most used Nonlinear Static Procedures for the seismic assessment of structures, since its introduction in 1975, when it was first presented by Freeman. More recently, this procedure was implemented in the ATC40 guidelines and lately improved in the FEMA-440 report. The first step of work addressed by this paper relates to the comparison between the two features of the CSM. In the second part, an extension of the FEMA-440CSM version … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 9 publications
0
13
0
1
Order By: Relevance
“…As mentioned before, preceding studies showed that plan-wise irregular buildings require 3-D modeling due to the torsional behavior under seismic excitation [13][14][15][16][17][18][19][20][21][22][23][24][25]. Structural schemes of Figure 3 provide evidence that one of the RC structures is irregular in plan.…”
Section: Applied Inelastic Static Proceduresmentioning
confidence: 96%
See 1 more Smart Citation
“…As mentioned before, preceding studies showed that plan-wise irregular buildings require 3-D modeling due to the torsional behavior under seismic excitation [13][14][15][16][17][18][19][20][21][22][23][24][25]. Structural schemes of Figure 3 provide evidence that one of the RC structures is irregular in plan.…”
Section: Applied Inelastic Static Proceduresmentioning
confidence: 96%
“…In the case where irregularities are dominant, those procedures are flawed, since they do not have a robust background. To overcome those deficiencies scientists developed 3D pushover techniques to take into account the torsional effects [13][14][15][16][17][18][19][20][21][22][23][24][25]. In their study Fajfar et al [16] stated that with an increase of plastic deformations the torsional effects tend to decrease.…”
Section: Introductionmentioning
confidence: 98%
“…The limit states of IO, CP, and GI are defined by FEMA 350. [39,40] As the IDA curve exhibits distinct elastic linear region, it signifies the IO structural performance level; in this stage, no damage in stiffness and bearing capacity occurs. With the increase of IM, softening segment is observed.…”
Section: Determination Of Failure Criteriamentioning
confidence: 97%
“…In this paper, limit states of immediate occupancy (IO), collapse prevention (CP), and global instability (GI) are adopted for evaluating seismic performance of hybrid structure. The limit states of IO, CP, and GI are defined by FEMA 350 . As the IDA curve exhibits distinct elastic linear region, it signifies the IO structural performance level; in this stage, no damage in stiffness and bearing capacity occurs.…”
Section: Incremental Dynamic Analysismentioning
confidence: 99%
“…Indeed, more recently, many studies aimed to define innovative methodologies [25][26][27][28][29] alternative to what is nowadays considered the most reliable approach: the Incremental Dynamic Analysis (IDA). In fact, IDA requires to perform a set of nonlinear response history analysis, on a detailed three-dimensional numerical model of the structure, for a set of ground motions, each scaled for various intensity levels, selected to cover a wide range of structural responses [8,9,30].…”
Section: State Of the Art Of Non Linear Static Proceduresmentioning
confidence: 99%